An Organocatalytic Asymmetric Nazarov Cyclization - Basak, Ashok K. (2010)
[Image: see text] An organocatalytic asymmetric Nazarov cyclization of diketoesters has been developed that proceeds by means of a dual activation mechanism. Screening of a number of catalysts led to a new thiourea that incorporates a primary amino group. The method gives rise to cyclic products with two adjacent quaternary asymmetric carbon atoms, one of which is an all carbon atom stereocenter, with complete or nearly complete diastereoselectivity, and in high or very high enantiomeric excess. A brief and very convenient synthesis of the acyclic diketoester starting materials through nucleophilic addition to a ketene has been described.